Pulsed signal properties of free‐ranging bottlenose dolphins (Tursiops truncatus) in the central Mediterranean Sea. Issue 3 (7th December 2014) - Buscaino, Giuseppa; Buffa, Gaspare; Filiciotto, Francesco; Maccarrone, Vincenzo; Di Stefano, Vincenzo; Ceraulo, Maria; Mazzola, Salvatore; Alonge, Giuseppe
Abstract This study describes pulsed signals from bottlenose dolphins of the central Mediterranean Sea. Data were collected during 2011 and 2012 in 27 surveys in the Sicilian Channel, during which 163 animals were sighted. Based mainly on the pulse repetition rate, the signals were classified as Low‐frequency click (LF; single clicks without a regular pulse rate), Train click (TC; with a interclick interval of 80 ± 2 ms), Burst (with a interclick interval of 3.4 ± 0.2 ms), or Packed click (with a lower number of clicks per train and median interclick interval of 3.2 ± 0.0 ms). The measured parameters were peak sound pressure level (SPLpk); signal duration; the 1st, 2nd, and 3rd peak of frequency; number of peaks frequency; bandwidth; centroid frequency; and the 10th, 25th, 75th, and 90th percentiles of the power spectrum distribution. Most of the parameters were significantly different among the groups, reflecting the different functions of these signals. LF clicks showed a lower peak frequency and percentiles and a longer duration and could be used to explore a wide area without a specific target focalization and with less resolution. The TC showed a higher SPLpk, higher peak frequency, lower duration, and lower number of secondary peaks frequency, showing a better resolution to investigate a specific target.